Answer: 1/4
===============================================
Step-by-step explanation:
We'll use the rule
x^y*x^z = x^(y+z)
This says that when we multiply exponential expressions with the same base, we add the exponents. In this case, the base is 2 so x = 2.
The exponents we're adding are -4 and 2
So,
2^(-4)*2^2 = 2^(-4+2) = 2^(-2)
This matches up with the a^b to show that a = 2 and b = -2
Furthermore, we'll use the rule that x^(-y) = 1/(x^y) to go from 2^(-2) to 1/(2^2) = 1/4 which is the value of c.